Ovary micromorphology and oogenesis in a rhyacodriline oligochaete (Clitellata: Naididae, Rhyacodrilinae). (21st February 2022) - Świątek, Piotr; Rodriguez, Pilar; Małota, Karol; Urbisz, Anna Z.
Abstract: The main goal of the article is to describe the ovary organization and oogenesis in Peristodrilus montanus, an aquatic oligochaete of the subfamily Rhyacodrilinae. The presented analysis will not only enrich the knowledge about how eggs are formed but, because of the suggested conservatism of ovary organization in clitellate annelids, can contribute to disentangling the complex phylogenetic relationships of the rhyacodrilines within Naididae. The paired, conically shaped ovaries are located in segment XI. They are composed of a dozen or so syncytial germ‐line cysts, which are associated with somatic cells. Each germ cell in a cyst has one intercellular bridge that joins it to a central and anuclear cytoplasmic mass, the cytophore. This pattern of cyst organization is typical for all clitellates that have been studied to date. Initially, the germ cells in a cyst undergo a synchronous development, however, there is no synchrony between cysts, and therefore there is a developmental gradient (oogonia, pre‐diplotene germ cells, germ cells in diplotene) of oogenesis along the long ovary axis. The cysts are composed of a maximum of 32 cells. Cysts with cells in diplotene detach from the ovaries and the extraovarian phase of oogenesis begins. The developmental synchrony is lost, one cell (an oocyte) per cyst starts to gather cell components and yolk and grows considerably. The remaining cells grow to some extent and function as nurse cells. Like in other microdriles, P. montanus oocytes are rich in yolk; other features of oogenesis are also similar to those that are known from other microdrile taxa. The system of ovary organization found in the studied species is broadly similar to the corresponding features known from Naidinae and Phreodrilidae and, to some extent, in Enchytraeidae. However, this system is different from the one that is known in Tubificinae, Limnodriloidinae and Branchiurinae. Abstract : We present the description of ovary micromorphology and the course of oogenesis in a representative of the subfamily Rhyacodrilinae, that is, Peristodrilus montanus . The scheme summarizes our results. (a) The ovary comprises a dozen or so germ‐line cysts (gc) which are morphologically similar and develop in synchrony. Each cyst is composed of 32 or lower number of cells arranged around the central cytophore (cy). The intraovarian phase of oogenesis is relatively short, and cysts detach from the ovary and float freely in the coelom; the extraovarian phase of oogenesis begins. (b–f) One cell in each cyst (an oocyte – oo) gradually gathers cell components and nutrients and grows considerably. In contrast, the rest of the cyst cells serve as nurse cells (nc), grow slightly and eventually detach from the late vitellogenic oocyte (lvo). Cells are depicted not in scale.